2014
DOI: 10.3389/fnut.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of BCMO1 Gene Variants on Macular Pigment Optical Density in Young Healthy Caucasians

Abstract: Background: Serum lutein (L) and zeaxanthin (Z) positively correlate with macular pigment optical density (MPOD); hence, the latter is a valuable indirect tool for measuring L and Z content in the macula. L and Z have been attributed antioxidant capacity and protection from certain retinal diseases but their uptake within the eye is thought to depend on genetic, age, and environmental factors. In particular, gene variants within beta-carotene monooxygenase (BCMO1) are thought to modulate MPOD in the macula.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…However, other studies have reported inconsistent findings; a positive correlation between central MPOD and central foveal thickness has been demonstrated [31], whereas others have found no correlation even when taking ethnicity into account [17, 31, 32]. In contrast, a significant negative correlation between central retinal thickness and MPOD at 0.5° (measured by HFP) was determined in a young healthy Caucasian cohort (r = -0.39, P = 0.01) [51]. The role of ethnicity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported inconsistent findings; a positive correlation between central MPOD and central foveal thickness has been demonstrated [31], whereas others have found no correlation even when taking ethnicity into account [17, 31, 32]. In contrast, a significant negative correlation between central retinal thickness and MPOD at 0.5° (measured by HFP) was determined in a young healthy Caucasian cohort (r = -0.39, P = 0.01) [51]. The role of ethnicity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies have confirmed the importance of genetic factors also in the MPOD response to supplementation [ 69 ]. In recent years, some of the genetic determinants of MPOD (variants in or near the GSTP1, SCARB1, ABCA1, BCG5, LIPC, ELOVL2, FADS1, FADS2, ALDH3A2, and RPE65 genes) have been identified [ 70 , 71 , 72 , 73 , 74 ], leading Meyers et al . to conclude that “MPOD is a multi-factorial phenotype associated with variation in genes related to carotenoid transport, uptake, and metabolism, independent of known dietary and health influences on MPOD” [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The values of MPOD are generally in the range of 0.30 -0.40 d.u 6,16,17,19,61 , with certain exceptions found in studies with mean values lower than 0.20 du. 60 or higher 62,63,65,66 . There are also differences observed in the form of expressing the results and, thus, in some cases the MPOD is expressed as a single value and other authors provide data on several loci, which, moreover, differ from one study to another.…”
Section: Insert Table 1 and Figure 1 Herementioning
confidence: 99%
“…In most of the studies included, the evaluation of the dietary intake of lutein and zeaxanthin measures them jointly and this intake has a mean value of between 1 and 2 mg/day. In some studies, it is the intake of foods that are good sources of lutein and zeaxanthin in the diet, either food groups such as fruit and vegetables [60][61][62] or specific foods such as Chinese wolfberry 63,64 or corn oil 63 , that is assessed in relation to the MPOD. With respect to the methodology utilized to evaluate the MPOD, the approach most widely used is heterochromatic flicker photometry, which has the limitations derived from being a psychophysical methodology, but its reliability has been the subject of a number of studies 49 .…”
Section: Insert Table 1 and Figure 1 Herementioning
confidence: 99%